2018
DOI: 10.1080/10438599.2018.1423765
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of productivity in Vietnamese SMEs: the role of management standards and innovation

Abstract: Using a rich panel dataset of small and medium scale manufacturing enterprises (SMEs) active in the manufacturing sector in Viet Nam, this paper investigates the drivers of firm productivity, focusing on the role played by international management standards certification. We test the hypothesis that, accounting for technological innovation (product and process) and other variables related to technological capabilities, international standards are conducive to higher productivity, through improved management pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 73 publications
(81 reference statements)
7
33
0
Order By: Relevance
“…For firm level performance, we investigate firms' sales growth, using empirical specifications from the industrial economics literature studying firm dynamics and explaining firm size distributions in developed and developing countries (Evans, 1987a(Evans, , 1987bSleuwaegen & Goedhuys, 2002;Sutton, 1997). This focus on sales growth and on domestically awarded certificates represents a novelty within the body of empirical literature on SMEs performance in Viet Nam, since empirical studies have, instead, looked at the effects of international certifications on other performance indicators, such as labour productivity (Calza, Goedhuys, & Trifković, 2019;Trifković, 2016), business risk (Trifković, 2018), work conditions (Trifković, 2017), and environmental performance (Nguyen & Hens, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For firm level performance, we investigate firms' sales growth, using empirical specifications from the industrial economics literature studying firm dynamics and explaining firm size distributions in developed and developing countries (Evans, 1987a(Evans, , 1987bSleuwaegen & Goedhuys, 2002;Sutton, 1997). This focus on sales growth and on domestically awarded certificates represents a novelty within the body of empirical literature on SMEs performance in Viet Nam, since empirical studies have, instead, looked at the effects of international certifications on other performance indicators, such as labour productivity (Calza, Goedhuys, & Trifković, 2019;Trifković, 2016), business risk (Trifković, 2018), work conditions (Trifković, 2017), and environmental performance (Nguyen & Hens, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To get a clearer understanding of the long-term effects of innovation and to check the results of this study for robustness, it would be desirable to see more research of this kind in the future. Finally, linking macroeconomic studies with the insights of the already existing microeconomic studies (Bourke & Roper, 2017;Calza et al, 2019;Wakke et al, 2015) might generate additional insights about the obviously complex and long-lasting impacts of standards.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the possession of an internationally recognized standard certificate leads to significant productivity. They also proposed that the effect of certification on productivity is particularly strong for firms with technological innovation [23].…”
Section: Four Key Industriesmentioning
confidence: 99%